PENGARUH FREE CASH FLOW, PROFITABILITAS, KEBIJAKAN LIABILITAS, DAN SIZE TERHADAP RETURN SAHAM - Lomanto, Lusiana; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of free cash flow, profitability, liability policy, and firm size to the stock return. This research is carried out by using real estate and property companies which are listed in Indonesia Stock Exchange in 2009-2013 periods as samples. The research samples have been obtained by using purposive sampling technique which is based on the determined criteria. The sample collection criteria are: 1) companies which are examined are the companies which are listed in IDX are engaged in the field of property and real estate in 2009-2013 periods, 2) companies which are engaged in the field of property and real estate have published and issued their financial statement completely in 2009-2013 observation periods, 3) companies which are engaged in the field of property and real estate have published and issued their financial statement in rupiah currency in 2009-2013 observation periods. Based on these criteria, 45 companies (225 firm year) have been obtained as samples. The analysis technique has been carried out by using multiple linear regressions. Based on the result of multiple linear regression analysis with 5% significancy level, the result of the research shows that: 1) free cash flow does not have any influence to the stock return, 2) profitability (ROA) has positive and significant influence to the stock return, 3) liability policy (DER) has positive and significant influence to the stock return, and 4) firm size does not have any influence to the stock return.Keywords: Free cash flow, Profitability, Liability Policy, Firm Size, and Stock Return